“In the hour of trial”: the spiritual life and socio-political issues in sermons Archimandrite Alexander (Lovchiy) - Murzin Evgenii (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
The article is devoted to the study of the Orthodox segment of the religious and social thought in Germany during the Third Reich. The basis of the research were «Sunday ﬂyers» — sermons compiled in the period of 1941–1945 by the prior of the st. Nicholas church in Munich, archimandrite Alexander (Lovchiy), one of the most prominent ﬁgures of Russian Orthodoxy. The article shows what the current issues the preacher cared about, demonstrates the speciﬁcity of his perception of the events. The author explores such themes as USSR and the Russian Orthodox Church, Christianity and national socialism, Russian emigration and its historic mission, science and religion, etc. Reﬂecting about the fate of Russia, Archimandrite Alexander appreciate happenings in the USSR as the punishment of God for anti-Church policy of the Bolsheviks. Нe compares Godless Soviet Russia and Russian Empire and dreams about its revival. He believes that the revival of the Empire is the duty of the Russian emigration. Simultaneously with the rejection of Communist ideology, Alexander criticizes and national-socialism and accuses its followers of trying to rehabilitate the paganism, hatred and cruelty. The preacher contrasts the ideas of racial superiority the gospel love, compassion and mercy, which constitute the moral basis of European civilization and guarantee its further development. He calls for the conviction of the authorities in cases when their actions are contrary to gospel principles. The article traces a parallel between denunciatory sermons rev. Alexander and leaﬂets, distributed in Bavaria by members of anti-fascist youth organization «White rose». Denunciatory sermons and leaﬂets have not only similar content. They also belong to the same period of time (The autumn of 1942). Based on the analysis of the content of leaﬂets and sermons, as well as speciﬁc historical circumstances, the autor suggestes that the relationship between Archimandrite Alexander and the leader of the «White rose» Alexander Scmorel, parishioner of the st. Nicolas church, has private and conﬁ dential nature